1989
DOI: 10.1002/ajim.4700150507
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota highway maintenance worker study: Cancer mortality

Abstract: Highway maintenance workers (HMWs) have been exposed to a broad range of potentially toxic substances, including diesel fuels and exhaust, asphalts and tars, herbicides, gasoline, polynuclear aromatic hydrocarbons, benzene, and lead. The number of current and former state, county, and municipal HMWs in the United States exceeds 500,000, yet the health risks of this occupation had never been studied. To fill this void and to respond to the public perception that Minnesota HMWs were at high risk of developing le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Case-control studies that were nested within cohort studies are discussed in the section on cohort studies of this review. All cohort studies discussed in the IARC report were included in our review, although some studies are not discussed in detail (Menck & Henderson 1976;Bender et al 1989;Van Den Eeden & Friedman 1993;Boffetta et al 1988Boffetta et al , 2001Birdsey et al 2010).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case-control studies that were nested within cohort studies are discussed in the section on cohort studies of this review. All cohort studies discussed in the IARC report were included in our review, although some studies are not discussed in detail (Menck & Henderson 1976;Bender et al 1989;Van Den Eeden & Friedman 1993;Boffetta et al 1988Boffetta et al , 2001Birdsey et al 2010).…”
Section: Study Selectionmentioning
confidence: 99%
“…The Minnesota Highway Maintenance Worker Study (Bender et al 1989) lacks detailed information on lung cancer mortality. The lung cancer SMR was 0.69 (95% CI: 0.52-0.90).…”
Section: Excluded Cohort Studiesmentioning
confidence: 99%
“…252 Several cohort, case-control and proportionate mortality studies have found no significant association of risk of multiple myeloma with exposure to diesel exhaust and/or engine exhaust, or occupations with the potential for such exposure. 28,43,89,90,116,[253][254][255][256][257][258][259] In an analysis of cancer mortality among women employed in ''fast-growing'' US occupations, a significantly elevated cancer-PMR was reported among teachers (PMR 5 1.23, 95% CI: 1.06-1.43). 260 Breslin et al 261 reported inverse associations for army (PMR 5 0.77, 95% CI: 0.23-2.53) and marine (PMR 5 0.45, 95% CI: 0.01-17.13) personnel serving in the Vietnam War.…”
Section: Other Occupational and Environmental Factorsmentioning
confidence: 99%
“…In addition, recent studies of U.S. highway maintenance workers demonstrate an excess risk of leukemia (31) and lymphopoietic cancer (32). Bender et al, who conducted the Minnesota Department of Transportation study (32) In response to my letter to The Lancet (6), Fleming (9) published a letter presenting analyses of peripheral blood counts among: adolescent boys and young men in Nigeria who inhale and swallow petrol while siphoning as "unofficial vendors" of petrol and heavy oil, motor mechanics employed in small workshops who use petrol as a solvent, official petrol pump attendants, and controls who were not exposed professionally to petroleum.…”
Section: Subsequent Diseasementioning
confidence: 99%